Utility of Tc-99m MDP bone SPECT in evaluation of osseous involvement in craniofacial malignancies. Issue 11 (November 2017) - Saeed, Shabana; Haq, Saif ul; Sohaib, Muhammad; Nawaz Khan, Ali
Abstract: Purpose: To assess the role of technetium-99m methoxy diphosphonate (Tc-99m MDP) single photon emission tomography (SPECT) imaging for the detection of osseous invasion in craniofacial malignancies. Material and methods: The study was performed in 45 subjects using Tc-99m MDP (740 MBq). Out of 45 subjects, 30 were patients had different craniofacial malignancies, and 15 subjects who did not have any malignancy served as controls. Planar imaging was performed. Anterior, lateral and oblique lateral views of the skull were obtained. SPECT imaging was done taking 64 views of the skull in a 360 ° circular path, each 40 s with 128 × 128 matrices. Scans were visually interpreted using a score of 0, 1, and 2, representing a lesion as definitely absent, doubtful, and definitely present, respectively. Planar scans were compared with the SPECT images. Results: Bone SPECT detected more lesions as compared to planar bone scan and plain radiographs. SPECT was found to be superior to planar imaging and radiographs in the detection and efficient demonstration of the extent of osseous invasion of craniofacial cancer. Sensitivity was 100% for SPECT and 83.33% for planar bone scan. Conclusion: SPECT imaging of the skull is a very beneficial complementary form of investigation in patients with craniofacial malignancies for the assessment of osseous invasion, particularly in tumors likely to invade the skull base. Highlights: In craniofacial malignancies, SPECT imaging can be an extremely useful complementary investigation for the assessment of osseous invasion, particularly in tumors likely to invade the skull base. SPECT picked up all the lesions efficiently but also was especially helpful in detecting the extent of osseous invasion particularly in patients with cancers near the skull base. Bone SPECT can be a valuable aid in the planning of surgical excisions of oral squamous cell carcinoma. Tc-99m MDP Bone SPECT picks bone invasion earlier than CT.